The effect of student learning environment towards academic achievement in UiTM Negeri Sembilan Branch Seremban Campus / Noor Aida Izati Borhanuddin, Noor Syahira Akmal Mohd Noor and Nur Azyra Izzati Adnan - Borhanuddin, Noor Aida Izati; Mohd Noor, Noor Syahira Akmal; Adnan, Nur Azyra Izzati (2021)
The aim of the study was to examine the effect of students learning environment towards academic achievement in UiTM Negeri Sembilan Branch Seremban Campus. The study collected data from students in UiTM Negeri Sembilan Branch Seremban Campus. 372 respondents were selected randomly as sample from three faculties: Faculty of Computer and Mathematical Sciences (FSKM), Faculty of Sports Science and Recreation (FSR), and Faculty of Administrative Science Policy Studies (FSPPP). In this study, online questionnaires were used to gather data and were validated using SPSS tools. A multiple linear regression model was used to evaluate the relationship between the independent variables such as Institution Environment, Psychological Environment and Home Environment with dependent variable (Academic Achievement). The results show that, Institution Environment and Home Environment have an effect towards students’ academic achievement while Psychological Environment does not have affect towards students’ academic achievement. The core ﬁndings of the study have a variety of implications for higher education and practice, measurement and theory development, and future research.